Food versus Fuel: An Updated and Expanded Evidence - Ondrej Filip; Karel Janda; Ladislav Kristoufek; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2017)
This paper replicates and extends the study of Zhang et al. (2010): 'Food versus fuel: What do prices tell us?" Energy Policy 38, pp. 445-451. We confirm the findings of the original paper that there was only a weak relationship between ethanol and food commodities in the period between March 1989 and July 2008. In addition, we extend that study and examine the cointegration relationship between biofuels and related commodities for a considerably enlarged dataset (3 vs. 1 market, 26 vs. 8 commodities, analysis up till 2017 vs. 2008, weekly vs. monthly data frequency). Focusing on the biofuel markets of Brazil, the EU and the USA in the three separate periods before, during, and after the food crisis of 2007 and 2008, we show that studying the time variation of the relationships plays an essential role in their proper understanding. Our results help to clarify the wide extensive discussion about the role of biofuels prices in food shortages manifested particularly during the food crises. In agreement with the original study, we confirm that price series data do not support strong statements about biofuels uniformly serving as main leading source of high food prices and consequently the food shortages.
Keywords: Q16; Q42; Q56; 330; biofuels; fuels; food; cointegration